The SCAN rule: a clinical rule to reduce CT misdiagnosis of intracerebral haemorrhage in minor stroke. - Lovelock, C; Redgrave, J; Briley, D; Rothwell, P (2010)
UNLABELLED: Many patients with minor stroke are referred to outpatient clinics and are not scanned immediately. A clinical rule is needed to identify patients who are likely to have intracerebral haemorrhage (ICH) and require urgent brain imaging and patients who can safely start antiplatelet agents before scanning. METHODS: Clinical factors associated with ICH were determined in 334 consecutive patients with minor stroke (National Institute of Health Stroke Scale score < or = 3), and a predictive model for ICH that was validated in a cohort of 280 patients presenting to a hospital-stroke clinic was derived. Prognostic value was quantified as the area under the ROC curve (c statistics). RESULTS: The proportion of ICH in minor stroke was 5.1% (95% CI 3.2% to 8.0%) in OXVASC, and 5.4% (3.3% to 8.7%) in the clinic cohort. Clinical factors predictive of ICH in OXVASC included blood pressure on initial assessment > or = 180/110 mm Hg (OR 14.5, 95% CI 1.8 to 114, p=0.001), vomiting (OR 15.7, 95% CI 5.4 to 46, p<0.001), confusion (OR 8.2, 95% CI 2.9 to 23, p<0.001) and anticoagulation use (OR 7.8, 95% CI 2.2 to 28, p=0.006), and at least one predictive factor was identified in all 17 patients with ICH and in 35% overall (c statistic 0.92, 95% CI 0.88 to 0.97). Therefore, we derived the SCAN rule to identify ICH if > or = 1 of the following were present: (S) severe hypertension, (C) confusion, (A) anticoagulation, (N) nausea and vomiting. In the clinic validation cohort, > or = 1 predictive factor was identified in 14/15 of patients with ICH and in 24% overall (c statistic 0.87, 95% CI 0.79 to 0.95). CONCLUSION: The SCAN rule appears to be specific and sensitive at identifying ICH in an independent cohort of patients with minor stroke, although further independent validations are needed.